Production of sodium lauryl sulfate from coconut oil - Gonda, Noel T.; Regalado, Raul C.; Tejano, Ana Rosalie V. (Diliman, Quezon City College of Engineering, 1981)
Plant: SLS Production Plant -- Location: Misamis Oriental -- Capacity: based on 300 operating days per year and a coconut oil raw material requirement of 36,000 metric tons annually, the yearly plant production are as follows - Sodium Lauryl Sulfate 16500 metric tons, Crude Glycerol 6900 metric tons -- Fixed capital investment: P 15,231,874 -- Total capital investment: P 33,119,924 -- Total product cost: 214,856,000 -- Total annual sales: P 228,616,000 -- % return on investment (after taxes): 29.5% -- Pay-off time: 3.39 years -- Break-even point: 43.58% of maximum capacity
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Soap factories; Surface active agents